Jean Gillon - artista-designer - Sacramento, Enock Fernandes; Latorraca, Giancarlo; Bueno, Graça; Teixeira, Ruy (Olhares, 2021)
Born in Romania and naturalized Brazilian, Jean Gillon (1919-2007) had an exciting life. He left his country fleeing Nazism, lived in Israel where he had a productive career in arts, scenography and interior design. Has lived in Brazil since the mid-1950s, he was a prominent figure in furniture design in the modern period, besides being a multiple creator with great production of interior projects, tapestries, sculpture, set design, objects and paintings. By unveiling his energetic trajectory, in addition to doing justice and shed light on his contributions, the book helps to connect the points of the history of design in Brazil. The book has the organization of the gallerist Graça Bueno, that for a decade has been organizing the collection of Gillon, texts by art critic Enock Sacramento, the curator Giancarlo Latorraca, from the gallerist Graça, and photo essay of Ruy Teixeira.
Ausstellungsdaten ermittelt: A partir do dia 12 de junho a 12 de dezembro de 2021, estará aberta a exposição "Jean Gillon: Artista-designer", uma realização do Museu da Casa Brasileira - instituição da Secretaria de Cultura e Economia Criativa do Estado de São Paulo – e da galeria Passado Composto Século XX
Keywords: Gillon, Jean -- 1919-2007; Gillon, Jean / 1919-2007 / Exhibitions; Furniture design / Brazil / Exhibitions; Tapestry / Brazil / History / Exhibitions; Furniture design; Furniture designers; Tapestry; Brazil; Biographies; Catalogs; Criticism, interpretation, etc; History; Bildband; Ausstellungskatalog -- Museu da Casa Brasileira -- 12.06.2021-12.12.2021 -- São Paulo